'Globesity'? The effects of globalization on obesity and caloric intake. (October 2016) - Costa-Font, Joan; Mas, Núria
Highlights: We examine the effect of globalization, in its economic and social dimensions, on obesity and caloric intake. We find a robust association between globalization and both obesity and caloric intake. We find that the primary driver is the 'social' rather than the 'economic' dimension of globalization. A one standard deviation change in social globalization increases obesity by 13.7 percent. Abstract: We examine the effect of globalization, in its economic and social dimensions, on obesity and caloric intake, namely the so –called 'globesity' hypothesis. Our results suggest a robust association between globalization and both obesity and caloric intake. A one standard deviation increase in globalization is associated with a 23.8 percent increase in obese population and a 4.3 percent rise in calorie intake. The effect remains statistically significant even after using an instrumental variable strategy to correct for some possible reverse causality and ommited variable bias, a lagged structure, and corrections for panel standard errors. However, we find that the primary driver (of the 'globesity' phenomenon) is the 'social' rather than the 'economic' dimension of globalization, and specifically the effect of changes in 'information flows' and 'social proximity' on obesity. A one standard deviation increase in social globalization increased the percentage of obese population by 13.7 percent.